Effective and safe control of glycemia with insulin Apidra - the recipe for success of type 2 diabetes prophylaxis - Elena Valer'evna Biryukova (Endocrinology Research Centre, 2011)
Current possibilities for the use of ultra-short acting insulin analogs are discussed. The importance of control of postprandial hyperglycemia is emphasized.Pharmacological properties of insulin glulisine are described with special reference to its advantage over human ultra-short acting insulin.An important characteristic of glulisine is the possibility of its efficacious use for the treatment of obese patients. The results of GINGER and CHOinternational studies suggest high efficacy and safety of glulisine used for intensive insulin therapy according to both flexible and fixed regimens.